FLUKTUASI HARGA KOMODITAS PANGAN DAN DAMPAKNYA TERHADAP INFLASI DI PROVINSI BANTEN - Astari Febriani Setiawan; Adi Hadianto (Journal of Agriculture, Resource and Environmental Economics, 2014)
Banten Province has a fluctuation inflation. The highest inflation is contributed by food category. Therefore, the price of food commodity become an important issue in the province of Banten. This research analyze the prices of food commoditiy, such as rice, corn, curly red chili,  onion, beef, chicken meat and layer egg. The purposes of this research are, to describe the food commodity price developments in Banten using descriptive analysis, to analyze fluctuations of food commodity prices and their impact on inflation in Banten using VAR models (Vector Autoregression), to analyze the inflation linkages between regions around Banten using Granger Causality. The results show the developments of commodity prices such as rice, corn, curly red chili, onion,beef, chicken meat and layer eggs generally showed an upward trend. VAR analysis results showed that in the short term only curly red chili which have a significant impact on inflation in Banten. On the long-term there are six commodities that impact significantly on inflation in Banten, those are beef, corn, rice, chicken meat, layer egg and red chili curly. The results of Granger causality test show that there is only one way relation that is Banten inflation affecting Lampung inflation.